Transformasi Pendekatan Katekese Moral Seksualitas di Era Digital: Analisis Kebutuhan dan Tantangan dalam Pembinaan Mahasiswa Katolik - Katarina Leba; Balthasar Watunglawar (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
This research examines the transformation of sexuality moral catechesis approaches in the digital era, particularly in the context of Catholic student formation. The primary focus is analyzing the needs and challenges in this transformation process. The methodology employed is a literature study with a qualitative approach, where researchers analyze various credible sources related to moral catechesis, digital education, and Catholic student formation. The research findings reveal that the success of transforming sexuality moral catechesis models is primarily determined by their ability to integrate Catholic moral values with contemporary digital realities. This includes developing adaptive learning methods and cultivating deep moral awareness among students. In the pastoral dimension, this transformation presents complex implications that necessitate the development of digital competencies for pastoral ministers. Additionally, a holistic approach is required to nurture the sexual morality of Catholic students.This research recommends program development based on systematic planning considering three essential aspects: content, methodology, and digital infrastructure. Such programs need to be equipped with effective evaluation systems and the development of supportive learning communities. The main contribution of this research is deepening the understanding of the importance of transforming catechesis approaches that can adapt to the digital era without sacrificing the integrity of Catholic moral teachings in the student formation process